2010
DOI: 10.3109/10715760903486065
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the photo-degradation of UV-filters and radical-induced peroxidation in cosmetic sunscreen formulations

Abstract: Photo-instability of common UV-filters is a well documented phenomenon. This study develops a method for concomitant measurement of photostability and photo-induced ROS generation in cosmetic formulations. Oil-in-water formulations containing three common UV filters (OMC, BMDBM, EHT), individually or combined, were further supplemented with phosphatidylcholine and exposed to UVA. All filters show spectral decrease after UVA exposure. OMC and EHT do not induce significant lipid-peroxidation (as measured by TBAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…Modern sunscreen formulations now incorporate organic UV filters, which are compounds designed to absorb specific wavelengths of ultraviolet radiation, namely UVA (320-400 nm), UVB (290-320 nm) or both UVA and UVB radiation [3]. These organic UV filters should remain stable during the entire period of sun exposure [4]; however, a number of UV filters are photochemically unstable, which can impair their absorbance after UV exposure. The most common UVA and UVB filters in sunscreens are avobenzone and OMC, respectively, although it has been shown that their combination is photounstable [5].…”
Section: Introductionmentioning
confidence: 99%
“…Modern sunscreen formulations now incorporate organic UV filters, which are compounds designed to absorb specific wavelengths of ultraviolet radiation, namely UVA (320-400 nm), UVB (290-320 nm) or both UVA and UVB radiation [3]. These organic UV filters should remain stable during the entire period of sun exposure [4]; however, a number of UV filters are photochemically unstable, which can impair their absorbance after UV exposure. The most common UVA and UVB filters in sunscreens are avobenzone and OMC, respectively, although it has been shown that their combination is photounstable [5].…”
Section: Introductionmentioning
confidence: 99%
“…For irradiation of formulations, the protocol described in [13] was used. Briefly, an amount equivalent to 50±2 mg (checked by weighing), as recommended by the COLIPA sun protection factor test method [27], was spread onto 25 cm 2 glass plates with a gloved finger, left to dry for 30 min in the dark, and then the plates were exposed to 15 min UVA as described above.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study was performed using a method reported elsewhere22 to evaluate lipid nanoparticle photoprotective effect against UVA radiation. Briefly, each formulation was loaded onto a 5 × 5 cm 2 glass (2 mg/cm 2 ) and spread with a gloved finger.…”
Section: Methodsmentioning
confidence: 99%